Treatment decision‐making among Canadian youth with severe haemophilia: a qualitative approach. (9th October 2014) - Lane, S. J.; Walker, I.; Chan, A. K.; Heddle, N. M.; Poon, M.‐C.; Minuk, L.; Jardine, L.; Arnold, E.; Sholapur, N.; Webert, K. E.
Summary The first generation of young men using primary prophylaxis is coming of age. Important questions regarding the management of severe haemophilia with prophylaxis persist: Can prophylaxis be stopped? At what age? To what effect? Can the regimen be individualized? The reasons why some individuals discontinue or poorly comply with prophylaxis are not well understood. These issues have been explored using predominantly quantitative rese‐arch approaches, yielding little insight into treatment decision‐making from the perspectives of persons with haemophilia (PWH). Positioning the PWH as a source of expertise about their condition and its management, we undertook a qualitative study: (i) to explore and understand the lived experience of young men with severe haemophilia A or B and (ii) to identify the factors and inter‐relationships between factors that affect young men's treatment decision‐making. This manuscript reports primarily on the second objective. A modified Straussian, grounded theory methodology was used for data collection (interviews) and preliminary analysis. The study sample, youth aged 15–29, with severe haemophilia A or B, was chosen selectively and recruited through three Canadian Haemophilia Treatment Centres. We found treatment decision‐making to be multi‐factorial and used the Framework method to analyze the inter‐relationships between factors. A typology of four distinct approaches to treatment was identified: lifestyle routine prophylaxis, situational prophylaxis, strict routine prophylaxis and no prophylaxis. Standardized treatment definitions (i.e.: 'primary' and 'secondary', 'prophylaxis') do not adequately describe the ways participants treat. Naming the variation of approaches documented in this study can improve PWH/provider communication, treatment planning and education.